2020
DOI: 10.1101/2020.06.15.153833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative interplay between biofilm formation and competence in the environmental strains ofBacillus subtilis

Abstract: 12 13 14 15a. These two authors contributed equally to this work. 16 (She contributed to about 50% of the results in the initial submission and the 17 revision; Hunter initiated the project and contributed to about 30% of the 18 results in the initial submission.) Abstract 31 Environmental strains of the soil bacterium Bacillus subtilis have valuable 32 applications in agriculture, industry, and biotechnology. They are capable of forming 33 robust biofilms and demonstrate excellent biological control activi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…A model such as this one was also proposed for the divergently overlapping comEA/EC and comER genes in B. subtilis [ 16 ]. In a more recent work [ 66 ], it has been shown that comER plays an important role in biofilm formation and sporulation, and that competence has a negative correlation with biofilm formation [ 67 ], supporting the stated hypothesis. When analyzing if the gene Mlut_14660 and the operon Mlut_14650/40/30 and their specific genetic context is conserved in other bacteria, we found that they are present and have the same or similar surroundings on the chromosomes of several different Actinobacteria genera (see Figure 5 ; only selection of chromosomal regions of related genera and species with similar gene arrangements depicted).…”
Section: Discussionsupporting
confidence: 55%
“…A model such as this one was also proposed for the divergently overlapping comEA/EC and comER genes in B. subtilis [ 16 ]. In a more recent work [ 66 ], it has been shown that comER plays an important role in biofilm formation and sporulation, and that competence has a negative correlation with biofilm formation [ 67 ], supporting the stated hypothesis. When analyzing if the gene Mlut_14660 and the operon Mlut_14650/40/30 and their specific genetic context is conserved in other bacteria, we found that they are present and have the same or similar surroundings on the chromosomes of several different Actinobacteria genera (see Figure 5 ; only selection of chromosomal regions of related genera and species with similar gene arrangements depicted).…”
Section: Discussionsupporting
confidence: 55%
“…In combining reporter constructs for the 14 genes of interest, we created 182 strains; this included all 91 possible pairwise combinations of the 14 genes in each of the two color orientations (e.g., both P hag - YPet ∷ amyE , P tapA - mTurq ∷ lacA and P tapA - YPet ∷ amyE , P hag - mTurq ∷ lacA to control for differences in fluorescent protein expression levels). Only six such dual-reporter strain pairs ( hag-tapA ; hag-sspB ; tapA-sspB ; srfAA-tapA ; skfA-tapA ; and tapA-comGA ) have been explicitly examined in the literature previously (23, 29, 30, 32, 33). All strains containing dual reporters grew similarly to wild-type B. subtilis (Figure S3).…”
Section: Resultsmentioning
confidence: 99%